When high viscosity of pancreatic cysts precludes effective EUS-FNA: a benchtop comparison of negative pressure devices - Walsh, Leonard T.; Mitchell, Lindsay; Johri, Ansh; Matone, Nicholas; Frecker, Mary; Moyer, Matthew (Endoscopy International Open, 2019)
Background and study aims Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) of pancreatic cystic lesions (PCLs) is an important diagnostic tool; however, it is often unsuccessful due to high viscosity of cystic fluid. In an effort to improve FNA, we objectively compared eight vacuum device configurations to determine the most effective method for aspirating viscous fluid collections. We also tested a high-frequency oscillation (HFO) technique that could be employed in FNA. Materials and methods Maximum gauge pressures of four vacuum devices were measured: two standard EUS-FNA syringes, a 50-cc Alliance II device, and a nonmedical hand vacuum pump. To aspirate a viscous stock solution, 19-gauge and 22-gauge needles were used and flow rates were calculated. HFO was also applied to the needle during aspiration to determine effect on aspiration rate. Results Aspiration devices generated maximum gauge pressures ranging from –21.5 to –27.5 inHg. The 19-gauge FNA needle aspirated viscous fluid 11.3 × faster on average than a 22-gauge needle. HFO increased average flow rates by 29.7 % in 19G and 124.6 % in 22G configurations. Conclusion EUS-FNA of viscous fluid can be optimized by using the lowest possible gauge needle and connecting a vacuum device capable of generating and sustaining near perfect vacuum. This can be accomplished by maximizing syringe volume. In addition, connector-tubing length between the syringe and needle should be minimized, and tubing wall should be sufficiently strong to resist collapse under vacuum. Other novel techniques to increase fluid yield include a hand vacuum pump and application of HFO to FNA.